Depiction of Women as Unfair Creatures in John Donne’s “Go and Catch a Falling Star”: Utilizing Norman Fairclough’s Model as a Research Tool in the Critical Discourse Analysis - Malik Umer Ajmal; Tayyaba Zainab (English Lecturers and Teachers Association (ELTA), 2024)
This research paper aims to study Norman Fairclough's three-dimensional model for a critical discourse analysis of John Donne's poem